2014
DOI: 10.3150/13-bej553
|View full text |Cite
|
Sign up to set email alerts
|

Goodness-of-fit test for noisy directional data

Abstract: We consider spherical data X i noised by a random rotation ε i ∈ SO(3) so that only the sample Z i = ε i X i , i = 1, . . . , N is observed. We define a nonparametric test procedure to distinguish H 0 : "the density f of X i is the uniform density f 0 on the sphere" and H 1 : " f − f 0 2 2 ≥ Cψ N and f is in a Sobolev space with smoothness s". For a noise density f ε with smoothness index ν, we show that an adaptive procedure (i.e. s is not assumed to be known) cannot have a faster rate of separation than ψ ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In the same framework, Lacour and Pham Ngoc (2014) showed that considering supersmooth noise and Sobolev class alternatives leads to only logarithmic separation rates. Let us see how introducing analytic classes change notably that conclusion.…”
Section: Asymptotic Results For Analytic Classesmentioning
confidence: 91%
See 4 more Smart Citations
“…In the same framework, Lacour and Pham Ngoc (2014) showed that considering supersmooth noise and Sobolev class alternatives leads to only logarithmic separation rates. Let us see how introducing analytic classes change notably that conclusion.…”
Section: Asymptotic Results For Analytic Classesmentioning
confidence: 91%
“…Proof The proof of this lemma is identical to the proof of Lemma A.3 in Lacour and Pham Ngoc (2014). Note that we deal with real valued quantities and do not need complex conjugation.…”
Section: Lemma A3 Suppose F ∈ a Pr (Q) Then The Bias Of U K Which mentioning
confidence: 90%
See 3 more Smart Citations